Intra-articular lipoma causing snapping in the patellofemoral joint - Yilmaz, Erhan; Karakurt, Lokman; Yildirim, Hanifi; Ozercan, Resat (My University, 2007)
Intra-articular lipoma is an exceedingly rare diagnosis. We identified a lipoma that was seated in the retropatellar area and caused snapping of the patella during flexion of the knee joint. The tumor was easily and totally excised under arthroscopic guidance after the thin pedicle was cut.
Keywords: Female; Humans; Joint Diseases; Knee Joint; Lipoma; Middle Aged; Patella; adult; arthroscopic surgery; arthrotomy; article; case report; female; follow up; human; intraarticular lipoma; joint aspiration; knee pain; knee radiography; lipoma; nuclear magnetic resonance imaging; patellofemoral joint; range of motion; arthropathy; knee; lipoma; middle aged; patella; pathophysiology